(3eQGJH GdhLhOs - (3YHO GdcQje Hf EHQGgje Hf YHO GdcQje GdLjdj GdUhaj , bWH GdOjf,J (B832 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi CYWi eQGJH GdhLhO MbgG Ydi GdJeGe hGdceGd CeG HYO aEf Chdi eG EYJfi Hg GdYbdGA hCYR eG UQa GdYeQ ai WdHg GdaVdGA gh GdYde s
(3BNQgG (B:s
(3GdeQJHI GdCQHYhf ef eQGJH GdhLhO gi ddEfSGf hHg JeJ GdeQGJH hced GdYGde dCfg YQa QHg eYQaI dfaSg hGddg Gdehab s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B50 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B313s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1650s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdTjN Ndjd GdNGdOi (B_ (3GdbOS s
Keywords: (3GdJUha hGdBOGH GdTQYjIs